Crossing the Role of Institutional Factors in the Process of Unemployment in Regional Labour Markets of Russia in 1995–2010 Роль институциональных факторов в процессах безработицы на региональных рынках труда России в 1995–2010 гг. - Kurzenev Vladimir A.; Perekrest Vladimir T. (Problemi Ekonomiki, 2012)
Some determinants of institutional unemployment are considered. Information and analytical technologies for labour market assessment and labour force quotation for regional labour markets are offered. Рассмотрены некоторые детерминанты институциональной безработицы. Предложены информационно-аналитические технологии для оценки труда и рынка рабочей силы, квотации на региональных рынках труда.